Fundamentalism and secularism : the Indian predicament - Nehring, Andreas; Gurukul Lutheran Theological College and Research Institute (Madras, India : Gurukul Lutheran Theological College & Research Institute, 1994)
Seminar papers.
Includes bibliographical references (p. [431]-434).
Keywords: Fundamentalism -- India -- Congresses; Secularism -- India -- Congresses; Religion and politics -- India -- Congresses